2021
DOI: 10.1097/cm9.0000000000001781
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis for acute ischemic stroke with extended time window

Abstract: Background: Intravenous thrombolysis (IVT) is an effective way for treating acute ischemic stroke (AIS). However, its effects have not been established among AIS patients with unclear stroke symptoms or with stroke onset for >4.5 h. Methods: We searched PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials and Google Scholar databases for randomized controlled trials that compared IVT (IVT group) and placebo or usual care (control group [CG]) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…25 IAT is established as an effective modality for the treatment of AIS. 26 However, END is reported to occur in 10% of AIS patients after IAT, which is an ominous clinical event tightly related to poor outcomes. 27 Therefore, early identification of END is beneficial for formulating personalized treatment strategies, thus optimizing the management of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…25 IAT is established as an effective modality for the treatment of AIS. 26 However, END is reported to occur in 10% of AIS patients after IAT, which is an ominous clinical event tightly related to poor outcomes. 27 Therefore, early identification of END is beneficial for formulating personalized treatment strategies, thus optimizing the management of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that patients who received intravenous thrombolysis treatment outside the recommended optimal window of 3-4.5 h from the onset of stroke symptoms, or in cases where the precise onset time was unknown, showed enhanced 90-day post-stroke mRS. However, this particular group also had a higher mortality rate when compared to individuals who did not undergo this treatment [18]. More recently, given that different patients have different physiology, it was noted to be feasible and safe, to have improved neurological function acutely, and to have increased the number of patients with an mRS of 0-1 [19].…”
Section: Introductionmentioning
confidence: 98%